ChemInform Abstract: Synthesis of Novel Polycyclic Heterosystems Based on 5‐Nitro[1, 2, 5]thiadiazolo[3, 4‐e]benzofuroxan. Issue 40 (16th September 2016) - Starosotnikov, Aleksei M.; Bastrakov, Maxim A.; Pavlov, Alexander A.; Fedyanin, Ivan V.; Dalinger, Igor L.; Shevelev, Svyatoslav A.
Abstract: Complex polycyclic compounds with potential NO‐donor activity are prepared utilizing Diels—Alder and Michael reactions.